Energy characteristics of plasma streams, generated by MPC - Astashynski, V.M.; Ananin, S.I.; Chebotarev, V.V.; Cherednychenko, T.N.; Ieliseiev, D.V.; Garkusha, I.E.; Kulik, N.V.; Ladygina, M.S.; Marchenko, A.K.; Morgal, Ia.I.; Petrov, Yu.V.; Solyakov, D.G.; et al. (Вопросы атомной науки и техники, 2013)
In present paper, results of experimental investigations of energy characteristics of plasma stream, generated by magnetoplasma compressor (MPC) are presented. It is shown that total energy contained in the plasma stream strongly depends on the discharge current, mass flow rate and sort of working gas. Radial distributions of energy density in plasma streams for different MPC modes of operations and energy transfer efficiency from the acceleration channel to the plasma stream are investigated.